The Strength of Restaurant Taxes in Garut Regency Through SWOT Analysis - Elsa Elpira; Lina Nurlaela; Muslim Al Kautsar (Entrepreneurship Faculty, Universitas Garut, 2023)
This study aims to determine the effectiveness and contribution of restaurant taxes in Garut Regency. The method used in this study is a qualitative method with a descriptive approach. Data collection methods are field studies, documentation, interviews and questionnaires. The method of data analysis used by the author is data reduction, presentation of data consultation drawing/verification. The analytical tool used is SWOT analysis. The results of this research show the effectiveness of the 2018-2021 restaurant tax in the